2022
DOI: 10.3389/fneur.2022.906249
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of α-hydroxybutyrate dehydrogenase with 1-year outcomes in patients with intracerebral hemorrhage: A retrospective study

Abstract: Background and aimsCardiac enzymes are recognized as a valuable tool for predicting the prognosis of various cardiovascular diseases. The prognostic value of alpha-hydroxybutyrate dehydrogenase (α-HBDH) in patients with intracerebral hemorrhage (ICH) was ambiguous and not evaluated.MethodsTwo hundred and thirteen Chinese patients with ICH participated in the study from December 2018 to December 2019. Laboratory routine tests and cardiac enzymes, including α-HBDH level, were examined and analyzed. All the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Additionally, our research has identified α-hydroxybutyrate as closely intertwined with sepsis, qualifying it as a risk determinant for sepsis and the subsequent 28-day mortality rate. Historical studies have attested to the association of α-hydroxybutyrate with a gamut of ailments including diabetes, insulin resistance, obesity, and heart failure ( 27 , 28 ). In certain contexts, it is perceived as a nascent biomarker for hypoxia and/or mitochondrial dysfunction ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our research has identified α-hydroxybutyrate as closely intertwined with sepsis, qualifying it as a risk determinant for sepsis and the subsequent 28-day mortality rate. Historical studies have attested to the association of α-hydroxybutyrate with a gamut of ailments including diabetes, insulin resistance, obesity, and heart failure ( 27 , 28 ). In certain contexts, it is perceived as a nascent biomarker for hypoxia and/or mitochondrial dysfunction ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which Coprococcus potentially influences sepsis could encompass several facets. Historically, studies have posited that Coprococcus can modulate the production of cytokines IL-1b and IL-6, thereby orchestrating the inflammatory response during an infection (26). Concurrently, Coprococcus is recognized as one of the principal bacteria responsible for butyrate production; butyrate, deemed a salubrious short-chain fatty acid, is pivotal for the health and functionality of colonic epithelial cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological outcomes were evaluated by the modified Rankin Scale (mRS) at one year post-aSAH using outpatient outcomes. At the end of the follow-up period, patients with mRS scores of 0-2 were considered to have good outcomes, and those with mRS scores of 3-6 were considered to have poor outcomes (Limin et al, 2022). was collected within 24 h of admission, and each sample was obtained in the fasted state.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, any intervention that reduces hematoma growth by 2 to 4 ml is equivalent to a 10% to 20% reduction in the risk of death or dependency within 90 days ( Chu et al, 2022 ; Delcourt et al, 2012 ). In clinical practice, accurately predicting the risk of HE is helpful for early targeted treatment or surgery ( Al-Shahi Salman et al, 2018 ), which can prevent adverse events, reduce patient mortality and disability rates, and have important clinical significance ( Limin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%